An object-oriented computational model to study cardiopulmonary hemodynamic interactions in humans. (June 2018) - Ngo, Chuong; Dahlmanns, Stephan; Vollmer, Thomas; Misgeld, Berno; Leonhardt, Steffen
Highlights: We introduced a comprehensive model of cardiopulmonary interactions (CPIs). This paper introduces: (1) an object-oriented non-linear model of the respiratory system and (2) a new concept of interconnecting the respiratory and the cardiovascular systems via physical connections available in object-oriented modeling languages. The model includes a cardiovascular system which was built up based on works that can be found in literature, extended by non-linear models of veins and capillaries. For the respiratory system, we developed and parameterized non-linear characteristics of model components based on the Mead parallel structure. The hemodynamic interaction was realized via a physical connection between two systems (pleural and interstitial pressures). The model is validated by qualitatively and quantitatively comparing the simulation results with data published in literature. Baseline simulation proved that the assigned parameters are consistent for a healthy human. Reasonable comparisons between simulation results and animal or clinical data demonstrated model usability in the quantitative prediction and study of CPIs. Our model is the first one to investigate cardiopulmonary interactions during mechanical ventilation and PEEP trials. Abstract: Background and objective: This work introduces an object-oriented computational model to study cardiopulmonary interactions in humans. Methods: Modeling was performed in object-oriented programing language Matlab Simscape, where model components are connected with each other through physical connections. Constitutive and phenomenological equations of model elements are implemented based on their non-linear pressure–volume or pressure-flow relationship. The model includes more than 30 physiological compartments, which belong either to the cardiovascular or respiratory system. The model considers non-linear behaviors of veins, pulmonary capillaries, collapsible airways, alveoli, and the chest wall. Model parameters were derisved based on literature values. Model validation was performed by comparing simulation results with clinical and animal data reported in literature. Results: The model is able to provide quantitative values of alveolar, pleural, interstitial, aortic and ventricular pressures, as well as heart and lung volumes during spontaneous breathing and mechanical ventilation. Results of baseline simulation demonstrate the consistency of the assigned parameters. Simulation results during mechanical ventilation with PEEP trials can be directly compared with animal and clinical data given in literature. Conclusions: Object-oriented programming languages can be used to model interconnected systems including model non-linearities. The model provides a useful tool to investigate cardiopulmonary activity during spontaneous breathing and mechanical ventilation.